Pengaruh Ukuran Embriozigot terhadap Regenerasi Beberapa Klon Kakao - Avivi, Sholeh; Restanto, Didik Pudji; Widyastuti, Tri (Jurnal Natur Indonesia, 2011)
This sesearch identified the responses of size of zygotic embryo of cocoa and to identify the responses of cocoaclone types toward ability to produce somatic embryo. The research was designed by Completely RandomizedFactorial Design within five replications. The first factors were the sizes of used explants, namely small (2-5 mm),average (6-9 mm) and big (10-15 mm). The second factors were cocoa clones, namely RCC 72, Sca 6, KW 162, KW163 and KW 165. The result showed that the best explant was the small size (2-5 mm) of cocoa zygotic embryo. Ithad significantly on number of rooting embryos and number of embryos with buds on rooting media. Clone RCC 72was the most responsive clone and could generate to be plantlet. Clone KW 165 performed the lowest response.